A Taxonomy of Attacks on Privacy-Preserving Record Linkage - Anushka Vidanage; Thilina Ranbaduge; Peter Christen; Rainer Schnell (The Journal of Privacy and Confidentiality, 2022)
Record linkage is the process of identifying records that corresponds to the same real-world entities across different databases. Due to the absence of unique entity identifiers, record linkage is often based on quasi-identifying values of entities (individuals) such as their names and addresses. However, regulatory ethical and legal obligations can limit the use of such personal information in the linkage process in order to protect the privacy and confidentiality of entities. Privacy-preserving record linkage (PPRL) aims to develop techniques that enable the linkage of records without revealing any sensitive or confidential information about the entities that are represented by these records. Over the past two decades various PPRL techniques have been proposed to securely link records between different databases by encrypting and/or encoding sensitive values. However, some PPRL techniques, such as popular Bloom filter encoding, have shown to be susceptible to privacy attacks. These attacks exploit the weaknesses of PPRL techniques by trying to reidentify encrypted and/or encoded sensitive values. In this paper we propose a taxonomy for analysing such attacks on PPRL where we categorise attacks across twelve dimensions, including different types of adversaries, different attack types, assumed knowledge of the adversary, the vulnerabilities of encoded and/or encrypted values exploited by an attack, and assessing the success of attacks. Our taxonomy can be used by data custodians to analyse the privacy risks associated with different PPRL techniques in terms of existing as well as potential future attacks on PPRL.